Fratture periprotesiche di femore: confine tra sintesi e revisione - franceschini, M.; De Bartolomeo, O.; Calabrò, F.; Cerbone, V.; Mineo, C.V. (Lo Scalpello - Journal, 2018)
PERIPROSTHETIC FEMORAL FRACTURES: THE BORDER BETWEEN SYNTHESIS AND REVISIONThe incidence of periprosthetic femoral fractures is increasing due to the growing number of THA all over the worldand the older age of the population. This article is a review of the literature and an analysis of our cases; the differentsurgical treatments were described and evaluated. Attention was paid to the border between synthesis and revision.